2022
DOI: 10.1080/21645515.2022.2045856
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent girls’ recommendations for the design of a human papillomavirus vaccination program in Sindh, Pakistan: a qualitative study

Abstract: Purpose Vaccination of adolescent girls against human papillomavirus (HPV) significantly reduces the incidence of cervical cancer. HPV vaccines are available in Pakistan but plans to develop HPV vaccination program are at a nascent stage. We conducted a formative study to explore adolescent girls’ knowledge and perspectives on HPV and cervical cancer and collect their recommendations for implementing an HPV vaccination program in their community. Methods Using qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…A US study showed some girls preferred seeing HPV vaccine information on the television rather than receiving information at their school, because they often watched TV together with their mothers which made it easier to bring up topic [73] highlighting the importance of providing vaccine information in a way that engages both parents and adolescents. In contrast, girls in a Pakistani study felt that television would not be an appropriate way to provide HPV information because it was mainly watched by men rather than women [74].…”
Section: Plos Global Public Healthmentioning
confidence: 94%
See 1 more Smart Citation
“…A US study showed some girls preferred seeing HPV vaccine information on the television rather than receiving information at their school, because they often watched TV together with their mothers which made it easier to bring up topic [73] highlighting the importance of providing vaccine information in a way that engages both parents and adolescents. In contrast, girls in a Pakistani study felt that television would not be an appropriate way to provide HPV information because it was mainly watched by men rather than women [74].…”
Section: Plos Global Public Healthmentioning
confidence: 94%
“…Many adolescents mentioned hearing about vaccines on the radio, television or on the internet. Social media was specifically mentioned in five studies (HPV, meningococcal vaccine) with four of these studies published in 2020 or later [33,63,[73][74][75].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Other frequently used information channels are instant messaging programs, Internet search engines, community health workers, and social media. In addition, there are less popular sources, including traditional healers and mass media such as news channels, television programs, and newspapers ( 86 ). Therefore, social mobilization is required to increase the acceptance of HPV vaccination among girls, parents, and respected influencers.…”
Section: Progression Of Hpv Vaccinementioning
confidence: 99%
“…They can be another key challenge in executing the HPV vaccination schedule ( 54 ). Moreover, parents’ skepticism about the HPV vaccine is the most likely obstacle to the successful implementation of the vaccination program in the community ( 86 ). It is clear that infrastructure issues, including supply shortages and staffing, have reduced access to medical services ( 90 ).…”
Section: Ongoing Challengesmentioning
confidence: 99%
See 1 more Smart Citation